The Role of Real-Time Business Intelligence in Supporting Digital Transformation and National Economic Resilience - Mar'atus Solikhah; Abdul Ahad (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
This study examines the strategic role of Real-Time Business Intelligence (RTBI) in supporting digital transformation and strengthening Indonesia's national economic resilience, by addressing the critical gap between rapid technological advances and institutional capacity to leverage data-driven decision-making for sustainable economic development. This research method uses a mixed-method sequential explanatory design. Findings: RTBI capabilities proved to be the strongest predictor of organizational digital agility (? = 0.742; p < 0.001), with 73.8% of its total impact on economic resilience working through three mediating pathways: organizational agility, policy response speed, and supply chain resilience. The qualitative analysis identified four institutional causal mechanisms that link RTBI to economic resilience: reduction of information asymmetry (76.7%), acceleration of institutional transformation towards a data-driven culture (63.3%), strengthening real-time fiscal stability monitoring (56.7%), and improved systemic risk detection capabilities (50.0%). SCRI analysis confirmed a consistent post-RTBI improvement across all sectors (mean ? = +12.6 points). Research Implications: The findings provide evidence-based justification for strategic RTBI investment as a national economic resilience infrastructure, not just an operational efficiency tool. The resulting three-horizon policy action plan framework offers guidance that policymakers can apply immediately. Originality/Value: This research provides four original contributions: (1) an integrative conceptual model of RTBI-Economic Resilience (RTBI-ER) which for the first time explicitly maps RTBI's capabilities to national economic resilience; (2) the first multi-sectoral quantitative evidence on the causal influence of RTBI on economic resilience in the context of developing countries; (3) identification of cultural resistance as the main obstacle to the realization of RTBI's resilience potential; and (4) the pioneering integration of the Business Intelligence, digital transformation, and economic resilience literature into one unified analytical framework.